Rift Valley Fever (RVF) decision support tool: Upgrades in 2024 - Dhulipala, Ram; Singh, Kanika; Bett, Bernard K. (International Livestock Research Institute, 2025)
Rift Valley fever (RVF) is a zoonotic disease caused by a virus that is transmitted by a wide range of mosquitoes. The disease mainly affects livestock and people. It has been listed by the World Health Organization as one of the nine diseases that has the potential to cause pandemics. RVF outbreaks are often sudden and intense, typically occurring after prolonged periods of heavy rainfall. These events are challenging to predict with sufficient lead time due to their rapid onset and progression. For instance, during the 2006-2007 RVF outbreak in East Africa, an early warning was issued in mid-September 2006, but a comprehensive warning only came in November 2006, by which time initial cases had already been reported. These delays in forecasting, combined with inadequate surveillance systems, have hindered the ability of public and animal health authorities to implement effective response measures. Post-outbreak assessments conducted in Kenya revealed that the epidemic's severity was aggravated by delays in recognizing the risks and taking preventive and control actions. The evaluations further highlighted the absence of a documented contingency or emergency plan for RVF, as well as the lack of pre-allocated emergency funds, especially in the livestock sector. These challenges underscored the need to refine contingency plans and led to the development of the RVF Decision Support Tool (DST) to enhance preparedness and guide responses to future epidemics. (Mbotha, D. and Bett, B. 2015)